Magnetic Resonance Imaging of Masticatory Muscles in Patients with Duchenne Muscular Dystrophy - Aranda-Ortega, N (W.B. Saunders Ltd, 2025)
Duchenne muscular dystrophy (DMD) is the most common muscular dystrophy in children. Impairment of masticatory function and swallowing disorders, potentially leading to aspiration and gastrostomy, are linked to fatty infiltration in the masticatory muscles, as previously observed in muscle ultrasound. This study aims to quantify muscle volume and fat fraction in muscle magnetic resonance imaging (MRI) in the masticatory muscles in non-ambulant DMD patients compared to healthy controls and evaluate their correlation with maximum bite force (MBF), which has not been previously described. Fifteen patients with DMD and 16 controls were included. MBF was measured with an oral dynamometer and total muscle volume (TMV) and fat signal fraction (FSF) were quantified using MRI with the Dixon technique. Four DMD patients presented with masticatory or swallowing difficulties. DMD patients had a significantly lower median MBF (141.8 N) compared with healthy controls (481.6 N, p < 0.0001). Additionally, median FSF was significantly higher in DMD patients (47.07 %) compared to controls (5.31 %, p < 0.0001). A strong negative correlation between TMV and MBF was observed in DMD patients (ρ = −0.70, p = 0.0048). A significant negative correlation between MBF and normalized FSF was observed in healthy controls (ρ = −0.5487, p = 0.300) and DMD patients (ρ = −0.5893, p = 0.0224). A non-significant positive correlation between age and FSF in DMD was detected (ρ = 0.38, p = 0.17). MBF, TMV and FSF quantified with the Dixon MRI are sensitive measures to evaluate masticatory function in DMD patients and may serve as biomarkers for clinical follow up. Studies in older patients are needed to evaluate the predictive role of MBF, TMV and FSF in the nutritional status of patients and the need for therapeutic interventions such as gastrostomy. © 2025 European Paediatric Neurology Society